Plant communities and diversity in boreal wooded fens: an ecoregional perspective - Locky, David (My University, 2009)
Ecoregions are increasingly being used as a framework for conservation planning. The Mid-Boreal Uplands Ecoregion stretches across western Canada from Manitoba to British Columbia. Within this Ecoregion (Manitoba to Alberta), we compared the plant communities and environmental variables in 80 sites of a single wetland type, wooded moderate-rich fen. Wooded moderate rich fens are a common boreal wetland, but among peatland types, are most likely to have the highest species diversity and number of rare plant species. Regional diversity totalled 273 species and was comprised of 86 bryophytes and 187 vascular plants. Total local diversity was greatest in Manitoba, and decreased in a longitudinal trend through Saskatchewan and Alberta. This may be related, in part, to the influence of orographic precipitation at Manitoba sites and to a decreasing gradient of growing degree days. Of the vascular plants in which provincial rarity information was available, ten species were observed across the Ecoregion. Ordinations and other analyses revealed distinct plant communities for all three locations, although bryophyte assemblages were more similar among locations than those of vascular plants. Bryophyte diversity increased with latitude and longitude, whereas vascular plant diversity decreased. Species composition over this continental scale exhibited a continuous change, even within a single wetland type in one Ecoregion. Conservation plans based on Ecoregion boundaries are preferable to political boundaries, but need to account for changes in abiotic conditions (e.g. precipitation) and biotic aspects (e.g., proximity to boundaries and transition zones).
Presented on June 25, 2009 at the Wetland Landscape Symposium of the Society of Wetland Scientists Annual Meeting in Madison, Wisconsin.
Keywords: ecoregions; boreal wooded fens; conservation planning; plant species